ANALISIS STRATEGI PENGEMBANGAN KOMODITI UBI JALAR DI DESA TOSOA DAN DESA TUGUAER KECAMATAN IBU SELATAN - Yunita Yunita; Zakeus Dadi; Musdhalifah Kholil (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2016)
The District of south Ibu is one of a large Product center of Sweet Potatoes in West Halmahera. On 2014-2015 years falled down in productivitied about 79 Ha to 53 ha. Tosoa and Tuguaer were included productivity village of sweet patatoes in south ibu district. This researche aimed to (1) To know the environment and profile of sweet patatoes farming in Tosoa and Tuguaer Village of South ibu District (2). To Identify the internal and external factors of sweety potatoes farming in Tosoa and Tuguaer Villages Of South Ibu district (3). To analyzis strategy position of sweety potatoes farming in Tosoa and Tuguaer Villages Of South Ibu district (4) To recomendate developed strategy of sweety potatoes farming in Tosoa and Tuguaer Villages Of South Ibu district. The primer and secunder datas were used in this researche. The Mixed method on this research with cuncurret triangulation approuching. The samples were token on 70 farmers as respondents. The technique of datas collecting were indeepth interview, Focus Disscusion Group, filling the quesioner, while analyizing the data used qualitative and quantitative. The results concluded that the position of sweety potatoes farming in Matrix IE to be on cuadrant IV these are Grouth and develop. The intensive and integrated were theright stategy in applicated. Based on analyzis of matrix SWOT there were 14 alternative of strategy which should be applied to develop and increase sweety potatoes farming.